2003
DOI: 10.1021/jp0305436
|View full text |Cite
|
Sign up to set email alerts
|

Search for Low Energy Structures of Water Clusters (H2O)n, n = 20−22, 48, 123, and 293

Abstract: A search for low energy structures of water clusters was performed with a combination of three computational tools: (a) temperature-dependent classical trajectories; (b) hydrogen network improvement; (c) rigid body diffusion Monte Carlo calculation on a smoothed potential energy surface. For the sizes of our main interest, n ) 48, 123, and 293, input configurations included spheroid structures cut from crystalline ice, and amorphous structures. For n ) 48, tube and sandwich minima were explored as well. The lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(138 citation statements)
references
References 89 publications
8
129
0
Order By: Relevance
“…This result was confirmed by vibrational IR spectroscopy experiments on pure water and Na-doped clusters [10,13], which suggest an onset of crystallization at about 275 water molecules [13]. Computer simulations support the assumption of amorphous-tocrystalline transition occurring above 200 molecules [14]. On the other hand, 21-molecule water clusters and sizes slightly above are likely to form more or less deformed cage structure; thus, a transition from cage to amorphous structures is expected to occur somewhere between 21 and 275 molecules.…”
Section: Introductionsupporting
confidence: 57%
“…This result was confirmed by vibrational IR spectroscopy experiments on pure water and Na-doped clusters [10,13], which suggest an onset of crystallization at about 275 water molecules [13]. Computer simulations support the assumption of amorphous-tocrystalline transition occurring above 200 molecules [14]. On the other hand, 21-molecule water clusters and sizes slightly above are likely to form more or less deformed cage structure; thus, a transition from cage to amorphous structures is expected to occur somewhere between 21 and 275 molecules.…”
Section: Introductionsupporting
confidence: 57%
“…For example, the lowest-energy structures of (H 2 O) n (n 9 1000) on the empirical potentialenergy surface have been reported, and these studies suggested that crystal cores are formed in the size region of a few hundred water molecules or more. [2][3][4]22] We show clear spectroscopic signatures for the abundance of the interior (4-coord) water. Furthermore, the fact that IR spectral patterns approach those of supercooled water and ice with increasing cluster size suggests formation of more ordered H-bonded network structures.…”
mentioning
confidence: 81%
“…15 In the DSI method as applied by Kazimirski and Buch, 51 all the oxygen-oxygen pair distances are calculated and sorted in ascending or descending order to get a vector of n(n À 1)/2 distances for n number of oxygen atoms from both structures. Then, the distance between these two vectors gives the DSI value.…”
Section: Mctbp Methods and Its Shortcomingsmentioning
confidence: 99%
“…50 Kazimirski and Buch used a molecular dynamics simulation and MC method on large water clusters. 51 One of the well-known MC optimization techniques, basin hopping, was rst applied to water clusters by Wales et al on (H 2 O) n , n # 21. 52 Kabrede did vibrational modes analysis in the basin hopping technique using TIP4P potential for water cluster optimization.…”
Section: 49mentioning
confidence: 99%